Pengaruh Kombinasi Contrast Bath dengan Elevasi Kaki 30o terhadap Derajat Pitting Edema pada Pasien Chf di Ruang Jantung Terpadu RSUD Dr. H. Abdul Moeloek Provinsi Lampung - Narda Riki; Tubagus Erwin; Novika Andora (Malahayati Nursing Journal, 2025)
ABSTRACT CHF has a high mortality and morbidity rate in the world, especially in developing countries. The prevalence of CHF in Indonesia in 2022 reached 5%, while in Lampung Province it was 1,2% or about 32,148 residents. Pitting edema is the most common symptom, which is experienced by about 80% of CHF patients. The impact of pitting edema can interfere with the patient's daily activities, discomfort, decrease physical mobility, changes in body posture, and increase the risk of falls in patients. One way to overcome pitting edema is with contrast bath therapy. The study was conducted with the aim of knowing the effect of the combination of contrast bath with 30o leg elevation on the degree of pitting edema in CHF patients.This research method uses a type of quantitative research, a quasi-experimental design with a non-equivalent control group. The population is all CHF patients who experience pitting edema at RSUD Dr. H. Abdul Moeloek Lampung Province, with a sample of 34 respondents and accidental sampling techniques. The independent variable is the combination of contrast bath with 30o leg elevation, while the dependent variable is the degree of pitting edema. Data analysis using independent t-test. The results of the univariate analysis obtained that the average degree of pitting edema in the group during the pretest was 2,41 ± 0.939 and posttest 1,41 ± 1,121. Meanwhile, in the control group during the pretest it was 2,59 ± 0,939 and posttest 2,35 ± 1,115. The results of the bivariate analysis obtained the effect of the combination of contrast bath with 30o leg elevation on the degree of pitting edema in CHF patients (p-value=0,02). Therefore, it is suggested for nurses to be able to integrate the combination of contrast bath with 30o leg elevation in the care protocol for CHF patients with pitting edema. Keywords: Combination of Contrast Bath With 30o Leg Elevation, Degree of Pitting Edema, CHF  ABSTRAK                                                                  CHF memiliki tingkat mortalitas dan morbiditas yang tinggi di Dunia terutama di negara berkembang. Prevalensi CHF  di Indonesia tahun 2022 mencapai angka 5%, sedangkan di Provinsi Lampung sebesar 1,2% atau sekitar 32.148 penduduk. Pitting edema merupakan gejala yang paling sering terjadi, dimana dialami sekitar 80% pasien CHF. Dampak pitting edema dapat mengganggu aktivitas pasien sehari-hari, ketidaknyamanan, menurunkan mobilitas fisik, perubahan postur tubuh, hingga meningkatkan resiko jatuh pada pasien. Salah satu cara untuk mengatasi pitting edema yaitu dengan terapi contrast bath. Penelitian dilakukan dengan tujuan diketahuinya pengaruh kombinasi contrast bath dengan elevasi kaki 30o terhadap derajat pitting edema pada pasien CHF. Metode penelitian ini menggunakan jenis penelitian kuantitatif, rancangan quasi eksperiment design dengan non equivalent control group. Populasi yaitu seluruh pasien CHF yang mengalami pitting edema di RSUD Dr. H. Abdul Moeloek Provinsi Lampung, dengan sampel sebanyak 34 responden serta teknik accidental sampling. Variabel independen yaitu kombinasi contrast bath dengan elevasi kaki 30o, sedangkan variabel dependen yaitu derajat pitting edema. Analisis data menggunakan uji-t independent. Hasil analisis univariat diperoleh bahwa rata-rata derajat pitting edema pada kelompok saat pretest adalah 2,41 ± 0,939 dan posttest 1,41 ± 1,121. Sedangkan pada kelompok kontrol saat pretest adalah 2,59 ± 0,939 dan posttest 2,35 ± 1,115. Hasil analisis bivariat diperoleh adanya pengaruh kombinasi contrast bath dengan elevasi kaki 30o terhadap derajat pitting edema pada pasien CHF (p-value=0,02). Oleh karena itu, disarankan bagi perawat agar dapat mengintegrasikan kombinasi contrast bath dengan elevasi kaki 30o dalam protokol perawatan untuk pasien CHF dengan pitting edema. Kata Kunci: Kombinasi Contrast Bath Dengan Elevasi Kaki 30o, Derajat Pitting Edema, CHF